Correlates Of Hypertension Among the Bank Employees of Surat City of Gujarat - Ashwinkumar M Undhad; P J Bharodiya; Rupalben P. Sonani (Medsci Publications, 2011)
Hypertension is becoming a public health emergency worldwide, especially in the developing countries. The job of bank employees is both sedentary in nature and accompanies high levels of mental stress, thereby at a higher risk of developing hypertension. The present cross-sectional study was conducted to find out the prevalence and the determinants of hypertension among bank employees of Surat city. Prevalence of hypertension was found to be 69.5%. Hypertension was significantly associated with age 45 years or more, alcohol intake, waist circumference, body mass index and diabetes.